Ford, the men and the machine. Robert Lacey - Lacey, Robert frey50 (Little, Brown Boston, Massachusettes, 1986)
The story of Henry Ford, the automobile company he created, and the3 dynasty he founded. The story of a handful of powerful individuals whose ambitions have helped shape modern American society.
Keywords: Henry Ford; Edsel Ford; Harry Bennett; Henry Ford II; Lee Iacocca; Ford -- Ford Motor Company; Cars -- Automobile industry